Development and Characterization of High‐Performance Sodium‐Ion Cells based on Layered Oxide and Hard Carbon. Issue 7 (27th June 2016) - Keller, Marlou; Vaalma, Christoph; Buchholz, Daniel; Passerini, Stefano
Abstract: The front cover artwork is provided by members of the "Electrochemistry for Batteries" group at the Helmholtz Institute Ulm (Germany). The image exemplifies the use of sodium‐ion cells with good overall electrochemical performance and their successful application in the power grid of the future. Read the full text of the Article at10.1002/celc.201600152 . Abstract : "The sodium‐ion battery technology is of very high interest for the smaller and more delocalized smart grid of the future, as it can help to utilize the complete potential of renewables. Keller et al. present a sodium‐ion cell comprising a layered oxide cathode and a hard carbon anode. The cell shows high energy efficiency and good electrochemical performance for 1000 cycles, which is an important step towards real applications of sodium‐ion batteries…" Find out more about the story behind the front cover research at10.1002/celc.201600152 .